Health Literacy in Patients’ Candidates or Submitted to Kidney Transplantation: An Integrative Literature Review - Montelo, Marcos Paulo Marinho; Teixeira, Jules Brito; Martins, Karine Anusca; Pereira, Edna Regina Silva (Brazilian Journal of Transplantation, 2023)
Objective: To describe the repercussions of health literacy (HL) in patients with Chronic Kidney Disease (CKD) candidates for orundergoing kidney transplantation (TxR). Methodology: Integrative review, carried out with the systematic selection of articles in the PubMed, Portal BVS and SciELO databases in August 2021. 62 articles were identified, of which 17 were selected for synthesis. Results: Most of the analyzed studies developed an observational or qualitative design. The limited HL has several impacts on patients’ decision-making processes, resulting in the postponement of insertion on the waiting list for TxR, refusal to perform this therapy and, in some situations, the death of the patient. Adequate HL is protective in several aspects of CKD patients’ lives, especially in the psycho-emotional and cognitive domains. Educational strategies, provided in the form of routine recommendations in dialysis centers or in addition to them, are essential for increasing HL. Conclusion: Patients who were candidates for or submitted to TxR had a high prevalence of limited HL, negatively impacting decision-making processes. Complementarily, the appropriate HL is recognized as essential for the conscious and shared decision-making process of the patient, as it empowers and enables the development of self-management in health.